CHEMICAL COMPOSITION OF PORTLAND CEMENT CLINKER - Jovliyev Ziyodulla Anvar Ogli (American Journals, 2023)
A summary of research on the composition of Portland cement clinker.
Keywords: portland cement, clinker, mineralogical composition, alite, belite, tricalcium aluminate, alumoferrite